UPAYA PENINGKATAN TEKNIK PASSING BOLA DALAM PERMAINAN SEPAKBOLA MELALUI METODE BERMAIN BERPASANGAN PADA SISWA KELAS VII.3 DI SMP NEGERI 1 KEDIRI - Pratama, Budiman Agung (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2018)
This study aims to improve the heading ball skills in soccer games through heading learning methods. This research is action research. The research subjects were class X.OTO.1 students of SMK Negeri 2 Somba Opu, which consisted of 28 male students and the analysis technique used was qualitative descriptive analysis. Based on the results of recapitulation between cycles after going through the implementation of heading learning methods in the second cycle shows that the skill of heading balls in soccer games in class X.OTO.1 students at SMK Negeri 2 Somba Opu has an increase, it is shown from the results in cycle I there are 5 students (17.9%) on a scale of 4 (good) and increased to 10 students (35.7%), resulting in an increase of 17.8% (35.7% - 17.9%). Likewise on the value scale 3 (medium category) shows that in the first cycle there were 10 students (35.7%) and increased to 18 students (64.3%) so that an increase of 28.6% (64.3% - 35, 7%). Thus it can be concluded that through the heading learning method carried out in the second cycle has an increase of 46.4% (17.8% + 28.6%) on heading skills in soccer games in class X.OTO.1 students in Vocational High School 2 Somba Opu. The results of the study concluded that: there was an increase in ball heading skills in soccer games through the heading learning method in class X.OTO.1 students at SMK Negeri 2 Somba Opu.